Part Three: The Quantitative Approach. Issue 10 (October 2015) - Quick, J; Hall, S
The previous articles in this series have explored the need for perioperative practitioners to select a research approach that supports the aims of the study to be undertaken (Quick & Hall 2015a, b). The quantitative approach is considered by some authors to be 'the epitome of the scientific approach' (Meadows 2003) and this article, the third in a series, aims to give an overview of this model.